1995
DOI: 10.1002/etc.5620140414
|View full text |Cite
|
Sign up to set email alerts
|

The association of DNA damage to concentrations of mercury and radiocesium in largemouth bass

Abstract: Largemouth bass from five lakes were examined to determine levels of contamination by mercury and radiocesium and amounts of DNA damage Concentrations of these toxicants and an index of body condition were regressed against over all DNA damage and DNA damage in individual tissues (liver, gills, and red blood cells) as indicated by the alkaline unwinding method Sample sites showed considerable heterogeneity in concentrations of mercury and radiocesium, as well as numbers of DNA strand breaks Generally, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
2
34
1
Order By: Relevance
“…Assuming this effect occurred in a similar manner as in humans (Mole 1958), it would be expected to significantly reduce life expectancies and survival in wild animals. Chronic radiation effects may also result in the development of chromosomal and (or) genetic aberrations (Hatch et al 1968;Bickham et al 1988;Lamb et al 1991;Sugg et al 1995) in addition to altered genetic structure of populations Shugart 1997, 1998;) in wild animals under radiation exposure from weapons test and development sites. While extremely limited data exist, reduced reproductive capacities in wild animals have been noted at detonation sites (Turner et al 1971;Medica et al 1973;Turner 1975;Turner and Medica 1977) consistent with the expected effects of radiation's impacts on the reproductive system (reviewed in Real et al 2004).…”
Section: Radiation Impactsmentioning
confidence: 99%
“…Assuming this effect occurred in a similar manner as in humans (Mole 1958), it would be expected to significantly reduce life expectancies and survival in wild animals. Chronic radiation effects may also result in the development of chromosomal and (or) genetic aberrations (Hatch et al 1968;Bickham et al 1988;Lamb et al 1991;Sugg et al 1995) in addition to altered genetic structure of populations Shugart 1997, 1998;) in wild animals under radiation exposure from weapons test and development sites. While extremely limited data exist, reduced reproductive capacities in wild animals have been noted at detonation sites (Turner et al 1971;Medica et al 1973;Turner 1975;Turner and Medica 1977) consistent with the expected effects of radiation's impacts on the reproductive system (reviewed in Real et al 2004).…”
Section: Radiation Impactsmentioning
confidence: 99%
“…Hartwig (1995) suggested that the mechanism for metal-induced breakage is the inhibition of repair processes while Sugg et al (1995) showed that adducted nucleotides produced by radiation may prevent the repair of naturally occurring strand breaks due to interference. This latter process occurs in addition to direct breakage from ionizing radiation or from induction of free radicals (Sugg et al 1995). Heavy metals may also cause direct breakage through the induction of oxygen radicals (Hoffman and Heinz 1998;Snow 1991;Tsuzuki et al 1994).…”
Section: Dna Double-strand Breakage (Ddsb)mentioning
confidence: 99%
“…In real situations, other pollutants whose combined effects on the interna1 processes are practically unknown almost always accompany radiopollution to which they may be subject. Recent studies have indeed showed the existence of synergic responses (Sugg et al, 1995;Ausseil et al, 2000;Fraysse et al, 2000), the ecological and evolutionary significance of which may be considerable. Finally, it may be increasing highlight importance to the effects which could appear in the long term, that is to say those which by largely exceeding the individual scale, may, through their reproduction, be expressed much later on the population scale.…”
Section: The D Q J U L I I E S Of a Holistic Approach To The Ecosystemmentioning
confidence: 99%
“…A large amount of literature exists on this subject, from the 1960's, which has been the dealt with in several reports often sponsored by international organisations (IAEA, 1976;1979;1988;1992;1995;NCRF', 1991;Rose, 1992;UNSCEAR, 1982;1996). This synthesis summarises to the main conclusions illustrated by some selected examples (for detailed references, see UNSCEAR, 1996).…”
Section: Radiation Effects On Biota Through External Irradiationmentioning
confidence: 99%